The impact of a1 resettlement scheme on natural resources utilization and management: the case of Ruchanyu resettlement scheme of Shurugwi South Ward 20b in Zimbabwe - Cheza, Enias (Midlands Sate University, 2015)
This study was conducted with the major thrust of assessing the impact of A1 resettlement scheme on natural resources utilization and management in Ruchanyu. Ruchanyu A1 resettlement scheme was established in 1992 through compulsory acquisition of land with compensation where the government acquired Otina and Pontevie to settle 80 families in four villages. During this time the district was stricken by severe droughts. As a result settlers turn to exploit the natural environment for survival through illegal good panning and wildlife poaching. Human and livestock population increased alarmingly. The researcher reviewed literature on background to land reform in Zimbabwe,A1 resettlement scheme, challenges faced by resulted farmers and their impacts to natural resources and weakness of available legal instruments on natural resources in Zimbabwe. The researcher made of qualitative and quantitative research design where questionnaire, interviews and direct participant observation were used a primary research tools. Sample random sampling and purposive sampling procedures were used to select respondents. Researchon the state of natural resources revealed that human and livestock population increases significantly, extensive areas of thorn and bush forest, massive pit and gulley erosion, siltation and water pollutionby activities of illegal gold panning, reluctant enforcement mechanism and stiff completion for grazing land amongst the four villages. Perceptions of small holder farmers as to how to improve the state of natural resources points to the need to include village chairmen on traditional leaders pay-role, resuscitation on VIDCOs, extension of remunerations to EMA subcommittees, establishment of village grazing units in communal grazing land among others.